The Relevance of the Concept of Islamic Parenting to the 2013 Curriculum and the Merdeka Curriculum in Early Childhood Education - Hapsari, Niken Kusuma; Khuluqi, Hasanal (GENIUS: Indonesian Journal of Early Childhood Education, 2023)
Children's behavior and personality are mainly influenced by their closest ones, families. Therefore, parents must understand various parenting strategies to nourish their offspring with as many good values as possible, especially those stemming from Rasulullah's practices (prophetic parenting). Parents and even teachers need to realize that to shape the younger Muslim generation, and they must rely heavily on the fundamental religious text of Islam, which are the Quran and Hadith, in their daily life and even in the schooling system. This qualitative study which was conducted as library research, focused on the concept of prophetic parenting from the perspective of Jamal Abdurrahman and Muhammad Nur Abdul Hafizh Suwaid, which then compared to two Indonesia curriculum documents, namely the 2013 curriculum and the Merdeka curriculum. It was found that: (1) the concept of prophetic parenting covered the aspects of child development and (2) the concept of prophetic parenting from Jamal Abdurrahman and Muhammad Nur Abdul Hafizh Suwaid's viewpoint was relevant to the six aspects of child development according to the regulation of the minister of education and culture of Indonesia Number 146 regarding the 2013 Curriculum – namely (a) moral and religious values development; (b) cognitive development, (c) physical and motor development; (d) language development; (e) social-emotional development; (f) art development, and the three learning outcomes in the Merdeka Curriculum in early childhood education level – namely, (a) character and religious values; (b) true-self; and (c) the basics of literacy and STEAM.   Abstrak Keluarga merupakan lembaga pendidikan pertama yang sangat berpengaruh pada pembentukan kepribadian anak. Untuk itu, dalam proses mendidik anak, kedua orang tua sudah sepatutnya memiliki ilmu dan wawasan terkait berbagai cara terbaik dalam mendidik anak; terutama metode mendidik yang merujuk pada Rasulullah saw (Prophetic Parenting). Hal ini dikarenakan untuk membentuk generasi muslim yang shalih, tentu tidak akan terlepas dari dua pondasi Islam yang utama, yaitu al-Quran dan al-Hadits. Fokus penelitian kualitatif dengan pendekatan library research ini adalah konsep prophetic parenting menurut Jamal Abdurrahman dan Muhammad Nur Abdul Hafizh Suwaid serta relevansinya terhadap enam aspek perkembangan sesuai dengan Permendikbud Nomor 146 tentang kurikulum 2013 Pendidikan Anak Usia Dini dan Kurikulum Merdeka pada satuan Pendidikan Anak Usia Dini. Hasil kajian menunjukkan bahwa: (1) konsep prophetic parenting yang ditawarkan oleh Jamal Abdurrahman dan Muhammad Nur Abdul Hafizh Suwaid mencakup beberapa aspek yang dibutuhkan dalam perkembangan anak usia dini; (2) konsep prophetic parenting yang ditawarkan oleh Jamal Abdurrahman dan Muhammad Nur Abdul Hafizh Suwaid relevan dengan enam aspek perkembangan anak usia dini sesui Peraturan Menteri Pendidikan dan Kebudayaan Republik Indonesia Nomor 146 tentang kurikulum 2013 Pendidikan Anak Usia Dini, antara lain (a) perkembangan nilai agama dan moral; (2) perkembangan kognitif, (c) perkembangan fisik motorik; (d) perkembangan bahasa; (e) perkembangan social emosional; (f) perkembangan seni serta tiga capaian pembelajaran Pendidikan Anak Usia Dini dalam Kurikulum Merdeka Pendidikan Anak Usia Dini, yaitu (a) nilai agama dan budi pekerti; (b) jati diri; dan (c) dasar-dasar literasi, matematika, sains, teknologi, rekayasa, dan seni (STEAM).